Nierozerwalność małżeństwa w rozumieniu Cerkwi prawosławnej - Rosochacki, Piotr Łukasz (Ius Matrimoniale, 2018)
Though the indissolubility of marriage is deeply rooted in the faith and the tradition of both the Catholic and Orthodox Churches, the understanding of this attribute of marriage is one of the differences in the doctrine on marriage in the teaching of the sister Churches. In the article the question of the indissolubility of marriage was presented from the point of view of teaching of the Orthodox Church with the detailed consideration given to the regulations of the Russian Orthodox Church (the Patriarchate of Moscow). Both the biblical and theological arguments were presented which gave the understanding of the indissolubility of the orthodox marriage, but also its eternal character. The author has shown the conflict which lays between the theological theory – teaching about the eternal marriage and the pastoral practice, which due to human weakness lets the new marriages to be blessed. “The sacrament of love” (as the marriage is often named in the orthodox theology) is for eternity – not only till the end of life, the article shows the actual juridical situation of the reasons for which the marriage could be dissolved. The article is a help to understand the teaching of the Orthodox Church in such an important sphere of the ecclesiastical law as the conjugal law.